Metaphor and metonymy in the digital age : theory and methods for building repositories of figurative language - Bolognesi, Marianna; Brdar, Mario; Despot, Kristina, 1978-; ProQuest (firma) (Amsterdam : John Benjamins Publishing Company, 2019)
This book describes methods, risks, and challenges involved in the construction of metaphor and metonymy digital repositories. The first part of this volume showcases established and new projects around the world in which metaphors and metonymies are harvested and classified. The second part provides a series of cognitive linguistic studies focused on highlighting and discussing theoretical and methodological risks and challenges involved in building these digital resources. The volume is a result of an interdisciplinary collaboration between cognitive linguists, psychologists, and computational scientists supporting an overarching idea that metaphor and metonymy play a central role in human cognition, and that they are deeply entrenched in recurring patterns of bodily experience. Throughout the volume, a variety of methods are proposed to collect and analyze both conceptual metaphors and metonymies and their linguistic and visual expressions.
Fantastic metaphors and where to find them -- Part I, New methods and digital resources for mining metaphor and metonymy in thought, language, and images -- 1. MetaNet -- 2. The tripartite typology and the Córdoba Metonymy Database -- 3. Metaphor in the age of mechanical production -- 4. VisMet and the crowd -- 5. MetaNet.HR -- Part II, Reflecting on the risks and challenges involved in building and using repositories of figurative language -- 6. The lexical vs. corpus-based method in the study of metaphors -- 7. Figurative reasoning in hedged performatives -- 8. Mereology in the flesh -- 9. Metaphor repositories and cross-linguistic comparison
Elektronická reprodukce.
Keywords: počítačová lingvistika; metafora; metonymie; digitální repozitáře; computational linguistics; metaphor; metonymy; digital archives; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online